Pengaruh Hipnoterapi Terhadap Stres Pada Pasien Gastritis Kronik Di Puskesmas - Safarina, Lina; Suganda Firmansyah, Yoggi; Rudyana, Hikmat (Jurnal Keperawatan Komplementer Holistic, 2024)
Chronic gastritis remains one of the most common serious pandemic infections, with deadly residual symptoms such as peptic ulcers or stomach cancer. This study uses a quasi-experimental design with a non-probability sampling technique. The results of the study show that the mean value before hypnotherapy was 23.40, which falls within the moderate stress range, and the mean value after hypnotherapy was 2.10, which falls within the normal stress range. Meanwhile, the mean value in the control group before the test was 25.90, which falls within the moderate stress range, and the mean value in the control group after the test was 23.40, which also falls within the moderate stress range. Statistical tests for the average stress levels of both groups on the third day yielded a p-value of 0.0001, indicating a difference in the average stress levels between the control group and the intervention group. This suggests that hypnotherapy has an effect on the stress levels of patients with chronic gastritis, meaning that the alternative hypothesis (Ha) is accepted. The results of this study can enhance knowledge about the effect of hypnotherapy on stress levels in patients with gastritis, thereby reducing stress. For community health centers (Puskesmas), it is necessary to develop and expand the application of this hypnotherapy method, as it is an easy and quick way to reduce and eliminate stress in patients with chronic gastritis, preventing the public from misjudging the practice of hypnotherapy.